DETERMINATION OF PROTEINS ASSOCIATED WITH COVID-19 BASED LIGAND DESIGNING AND MOLECULAR MODELING - Fatemeh Mollaamin (Journal of the Chilean Chemical Society, 2022)
Towards to recognize a strong inhibitor we accomplished docking studies on the major virus protease with 4 natural product species as anti Covid-19(SARS-CoV-2), namely “Vidarabine”, “Cytarabine”, “Gemcitabine” and “Matrine” from which are extractive from Gillan’s leaves plants. These are known as Chuchaq, Trshvash, Cote-Couto and Khlvash in Iran.  Among these four studied compounds, Cytarabine appear as suitable compound with high effectiveness inhibitors to this protease. With docking simulation and NMR investigation we demonstrated, these compounds exhibit a suitable binding energy around 9 Kcal/mol with various ligand proteins modes in the binding to COVID-19 viruses. However, these data need further in both, vivo & vitro evaluation for repurposing these drugs against COVID-19 viruses.